Binge-Like Eating Is Not Influenced by the Murine Model of OPRM1 A118G Polymorphism - Sachdeo, Bryn L. Y.; Yu, Lei; Giunta, Gina M.; Bello, Nicholas T. (Frontiers in Psychology, 2019)
Impairments in opioid receptor signaling have been implicated in disordered eating. A functional variant of the OPRM1 gene is a guanine (G) substitution for adenine (A) at the118 position of exon 1 (A118G). The influence of the A118G variant on binge eating behaviors and the effectiveness of pharmacotherapies used to treat binge eating have not been characterized. Mice were generated with A to G substitution at the 112 position on exon 1 to produce a murine equivalent of the human A118G variant. Homozygous female mice (AA or GG) were exposed to intermittent access to a highly palatable sweet-fat food with or without prior calorie deprivation to promote dietary-induced binge eating. There were no genotype-dependent differences in the dietary-induced binge eating. However, GG mice exposed to intermittent calorie restriction (Restrict) had higher body weights compared with GG mice exposed to intermittent sweet fat food (Binge) and ad libitum feeding (Naive). Acute oral dosing of lisdexamfetamine (0.15, 0.5, and 1.5 mg/kg) or sibutramine (0.3, 1, 3 mg/kg) did not produce genotype-dependent differences in binge-like eating. In addition, no genotype-dependent differences in binge-like eating were observed with chronic (14-day) dosing of lisdexamfetamine (1.5 mg/kg/day) or sibutramine (3 mg/kg/day). In the chronic dosing, body weights were higher in the GG Restrict compared with AA Restrict. Our findings suggest that the A112G polymorphism does not influence binge eating behaviors or pharmacotherapies for treating binge eating.